English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please show work 10 points

2007-01-28 08:23:44 · 3 answers · asked by grim reaper 2 in Science & Mathematics Mathematics

3 answers

That's so easy, even a CAVEMAN can do it.

2007-01-28 08:28:31 · answer #1 · answered by Anonymous · 0 0

distribute the - thru the second set of ()
3+2i-3-2i=0
since 3-3=0 and 2i-2i=0
in standard form it would be 0+0i

2007-01-28 16:31:55 · answer #2 · answered by dla68 4 · 0 0

(3 + 2I) - (3 + 2I)

3+ 2I - 3 - 2I

3 - 3 = 0

2I - 2I = 0

- - - - - - - - - - - -S-

2007-01-28 16:59:05 · answer #3 · answered by SAMUEL D 7 · 0 0

fedest.com, questions and answers